Strategy for Developing Quality of Dakwah With Theory of Guidance and Counseling of Youth Muhammadiyah - Gusman Lesmana (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
In preaching, each individual has an obligation to spread goodness to everyone to jointly do good things in life to create harmony and comfort in living together. In this case, da'wah activities need to be trained and developed for individuals when they are young and adolescents so that preaching skills are more mature and of good quality. This research was conducted with the aim to train da'wah to reconnect human nature with religion or make people aware of the truth of Islam and practice the teachings of Islam, so that they become good people. Making a good person means saving that person from heresy, from ignorance and poverty and from backwardness. The results of this study are to combine the da'wah process with counseling which is classified as a helping process but not just giving advice. In the process of helping, counselors need to foster, guide clients to better understand about themselves, their abilities, abilities, and abilities. With this he will be guided so that he can design for the future. All client decisions and choices are not from the counselor but from the client itself. The counselor's role is only to guide the client in the process of making decisions and choices